UPAYA PEMBENTUKAN PERILAKU PENEGAK HUKUM YANG ANTI KORUPSI MELALUI REKAM SIDANG TIPIKOR - Ridwan Ridwan (Masalah-Masalah Hukum, 2014)
Corruption is a criminal act. Corruption causing state unable to fulfill  its legal duty; to protect and to welfare his society, in those conditions states wouldn't be able delivering happiness for the people. Corruption recently in Indonesia is involving all society element, including the law enforcement officer. Furthermore, some verdicts describing un- responsive and un-progressive decisions, then make this verdict having no quality and fairness. These realities, motivating KPK RI (.....) take some real steps in preventing and combating corruption through court recording activity in any corruption case at the court; prosecutor could be from KPK or district attorney with specific circumstances, the case get much public attention; because of its actor or how big government loss. Court records during court session over corruption case has improved some law enforcement officer behavior for not doing corruptive. It has also become an effective tool for arising social control which is a part of corruption eradicating.